Ethnomedicine for fevers by the tribes of Visakhapatnam district, Andhra Pradesh - M. Hari Babu; T.V.V.Seetharami Reddi (Journal of Traditional and Folk Practices (JTFP), 2016)
The paper deals with 66 species of plants covering 62 genera and 38 families used by the tribes of Visakhapatnam district for curing fevers under 75 practices. Leguminosae is the dominant family with 10 species followed by Apocynaceae (6 spp), Lamiaceae (5 spp) and others. Habit-wise analysis showed the dominance of herbs with 23 species followed by trees (19 spp), shrubs (16 spp) and others. Root is used in most of the practices (28) followed by leaf (19), stem bark (13) and others. Polyalthia suberosa and 27 practices were found to be new